Leveraging Gamification Mechanics for Students’ Learning Motivation in Higher Education - Bogonko, Ben Mariga (Indonesian Journal of Education and Mathematical Science, 2026)
The purpose of this paper was to analyze the effect of integrating gamification mechanics in Learning Management Systems (LMSs) for students’ motivational learning experience in higher education institutions. The study was anchored on both Self-Determination theory and the theory of gamified learning. The target population was 162 respondents. Questionnaires and Modular Object-Oriented Dynamic Learning Environment (MOODLE) reporting logs were used for data collection. Descriptive and inferential techniques were used in data analysis. The results were presented in tables and figures. The results established that gamified LMS students were more motivated compared to the non-gamified LMS students. The study confirmed that the application of gamification had a positive influence on students’ motivation. The investigation suggests that eLearning instructors receive training through workshops on gamification integration for their courses from the university management. Besides, the eLearning Directorate should create a precise guideline on how gamification tools might be integrated into the university course curricula to improve students’ engagement and concentration in learning activities.